2022
DOI: 10.3389/fimmu.2022.970949
|View full text |Cite
|
Sign up to set email alerts
|

A novel T-cell proliferation-associated regulator signature pre-operatively predicted the prognostic of bladder cancer

Abstract: BackgroundBladder cancer (BCa) is a remarkably malignant and heterogeneous neoplastic disease, and its prognosis prediction is still challenging. Even with the mounting researches on the mechanisms of tumor immunotherapy, the prognostic value of T-cell proliferation regulators in bladder cancer remains elusive.MethodsHerein, we collected mRNA expression profiles and relevant clinical information of bladder cancer sufferers from a publicly available data base. Then, the LASSO Cox regression model was utilized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In the original study, most of these TPRGs have been demonstrated to increase the proliferation cancer analysis shows that oncogene CDK1 is an immunological and prognostic biomarker, which may influence tumor immunity mainly by mediating the migration of immune cells to TME, and is positively associated with tumor mutational burden and microsatellite instability (54). CXCL12 is highly enriched in fibroblasts (16). Fibroblasts in bladder cancer parietal tissue promote bladder carcinogenesis and progression by paracrine secretions of CXCL12 into TME to interact specifically with CXCR4 receptors (a specific receptor for CXCL12, expressed in T cells and macrophages in tumor tissues) and promote the proliferation of depleted T cells in cancer tissues (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the original study, most of these TPRGs have been demonstrated to increase the proliferation cancer analysis shows that oncogene CDK1 is an immunological and prognostic biomarker, which may influence tumor immunity mainly by mediating the migration of immune cells to TME, and is positively associated with tumor mutational burden and microsatellite instability (54). CXCL12 is highly enriched in fibroblasts (16). Fibroblasts in bladder cancer parietal tissue promote bladder carcinogenesis and progression by paracrine secretions of CXCL12 into TME to interact specifically with CXCR4 receptors (a specific receptor for CXCL12, expressed in T cells and macrophages in tumor tissues) and promote the proliferation of depleted T cells in cancer tissues (16).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 is highly enriched in fibroblasts (16). Fibroblasts in bladder cancer parietal tissue promote bladder carcinogenesis and progression by paracrine secretions of CXCL12 into TME to interact specifically with CXCR4 receptors (a specific receptor for CXCL12, expressed in T cells and macrophages in tumor tissues) and promote the proliferation of depleted T cells in cancer tissues (16). Those subtypes divided by the risk model showed remarkably differences in biology function and pathway, mutation status, immunity and drug susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, T‐cell‐based anticancer immunotherapies have brought substantial benefits to many patients, and the clinical effectiveness changes remarkably across tumour types [ 40 ]. However, the crosstalk between the TME and tumour could functionally reprogramme and sculpt the TME.…”
Section: Discussionmentioning
confidence: 99%